2018
DOI: 10.1007/s11427-017-9232-6
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing confirms molecular diagnoses in 38 Chinese families with hereditary spherocytosis

Abstract: Hereditary spherocytosis (HS), the most common cause of congenital hemolytic anemia, is caused by deficiency of the erythrocyte membrane proteins. Five causative genes (ANK1, SPTB, SPTA1, SLC4A1, and EPB42) have been identified. To date, molecular genetic studies have been performed in different populations, including the American, European, Brazilian, Japanese and Korean populations, whereas only a few studies have been described in the Chinese population. Here, by reanalysis of the exome data, we revealed ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 36 publications
2
49
1
Order By: Relevance
“…All identified variants (21, among which 13 novel) were classified as likely pathogenic or pathogenic loss-of-function mutations. A recent exomic study of 38 Chinese patients with suspected HS found mutations of ANK1 or SPTB in all patients [24]. Gallagher et al in 2019 [25] reported on a group of 24 recessive HS patients explored by WES and whole genome sequencing (WGS), all having mutations found in SPTA1.…”
Section: Discussionmentioning
confidence: 99%
“…All identified variants (21, among which 13 novel) were classified as likely pathogenic or pathogenic loss-of-function mutations. A recent exomic study of 38 Chinese patients with suspected HS found mutations of ANK1 or SPTB in all patients [24]. Gallagher et al in 2019 [25] reported on a group of 24 recessive HS patients explored by WES and whole genome sequencing (WGS), all having mutations found in SPTA1.…”
Section: Discussionmentioning
confidence: 99%
“…Hereditary spherocytosis (HS), one of the most common monogenic haemolytic anaemia diseases, is characterized by spherical‐shaped erythrocytes in the peripheral blood of patients. Hereditary spherocytosis is prevalent worldwide, especially in the Northern European population, with an incidence rate of 1:2000 . To date, no exact epidemiological data related to HS in China are available, and the estimated prevalence is 1.27/100 000 in males and 1.49/100 000 in females, which was reported by Wang et al only …”
Section: Introductionmentioning
confidence: 92%
“…Moreover, a molecular diagnosis is essential when the clinical diagnosis is not certain, for example in patients that require frequent transfusions. Genetic testing for RBC defects is moving increasingly towards customised multi‐gene panels (i.e., targeted‐NGS) and whole‐exome sequencing (Roy et al , ; Russo et al , ; Wang et al , ). The diagnostic yield of targeted‐NGS approach ranges between 40% and 65% of screened patients, depending on the number of genes included in each panel (Roy et al , ; Russo et al , ).…”
Section: New Insights Into the Diagnosis Of Red Cell Membrane Disordersmentioning
confidence: 99%